Synthesis and Characterization of Biotene: A New 2D Natural Oxide From Biotite (Small 27/2022). Issue 27 (7th July 2022) - Mahapatra, Preeti Lata; Tromer, Raphael; Pandey, Prafull; Costin, Gelu; Lahiri, Basudev; Chattopadhyay, Kamanio; P. M., Ajayan; Roy, Ajit K.; Galvao, Douglas S.; Kumbhakar, Partha; Tiwary, Chandra Sekhar
Abstract : Green Energy In article number 2201667, Douglas S. Galvao, Partha Kumbhakar, Chandra Sekhar Tiwary, and co‐workers convert dust crystals of biotite ores from mountains into atomically thin two‐dimensional materials using liquid exfoliation. Two‐dimensional‐biotite can be utilized to harvest small force/pressure or strain for generating green electricity.